Inhibition Test of Noni Fruit Extract (Morinda citrifolia) toward Fungal Isolates that Cause Dandruff - Ambarwati Ambarwati; Tanti Azizah; Sujono Sujono; Retno Sintowati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Dandruff  is  the most head skin problem. If it does not treatment as possible as, dandruff can cause hair drop off. Dandruff  is  caused by microorganism, especially fungal. Noni (Morinda citrifolia) fruit has an activity as antifungal. The aim of this research was to know the inhibition effect of Noni extract toward fungal isolates that can cause dandruff. This research was exploration research. The steps in this research included : (1). Isolation microorganism from dandruff on Potatos Dextro Agar media by Spread plate methode. (2). Purification was done to get a pure fungi isolate by streak plate methode. (3). Made Noni extract. (4). Inhibition test of Noni extract toward fungal isolates by paper disc methode. Based on this research, there were 18 fungal isolates from the purification. Three isolates was knowen as kapang and 15 isolates as yeast. Noni extract could inhibit the grow of 14 fungal isolates with diameter of inhibition zone about 10 until 35 mm. Seven isolates could be blocked with strong category (the diameter of inhibition zone ≥ 25 mm), namely : J4 (30 mm), J5 (35 mm), J8 and J16 (26 mm), J13 (33 mm), J14 (25 mm),  and J18 (28 mm). The conclusion of this  research is Noni fruit extract can be used as an alternative medicine to treatment dandruff. Keywords: Noni fruit extract, antifungal, dandruff